Chiral induced synthesis of helical polypyrrole (PPy) nano-structures: a lightweight and high-performance material against electromagnetic pollution - Xie, Aming; Wu, Fan; Jiang, Wanchun; Zhang, Kun; Sun, Mengxiao; Wang, Mingyang (Journal of materials chemistry. C, Materials for optical and electronic devices, 2017)
Helical conducting polymer nano-structures have attracted increasing attention because of their superior optical and electrical activities, lightweight, and flexibility as well as controllable morphologies at several levels of a hierarchy. Nevertheless, hardly any research has focused on helical conducting polymer nano-structure based electromagnetic protecting materials. Herein, we synthesized single-handed helical polypyrrole (PPy) nano-structures by a chiral inducing route and demonstrated their amazing electromagnetic protecting abilities. A gradually constructed conducting network and helical chirality may be the main reasons for the tunable and impressive electromagnetic protecting performance of the as-prepared helical PPy nano-structures. This research opens up an opportunity for the application of single-handed helical conducting polymer nano-structures as a lightweight and tunable high-performance electromagnetic protecting material, especially in the fields of special aircraft, aerospace and fast-growing next-generation flexible electronics.